Kerjasama (Syirkah) Penyedia Jasa Tiket Dengan Penyedia Jasa Transportasi di Panyabungan Dalam Analisis Hukum Islam - Hamid , Asrul (Prodi Hukum Ekonomi Syari'ah STAIN Mandailing Natal, 2021)
Cooperation (syirkah) between CV owners. A ticket service provider with the owner of a transportation service provider on travel transportation in Panyabungan, namely where CV. Maharani Travel with travel car owners divides profits of 70% and 30% for car owners. And CV. Mandiri Taxi divides the profit of 45% for the company and 25% for the car owner and 30% for the driver and if there is an accident or things that are detrimental then from both CVs. the travel stated that the bearer of the loss was the owner of the CV. the largest travel agent and the driver, while the owner of the travel car is not responsible. According to the view of Islamic law on the practice carried out by CV. Maharani Travel with travel car owners and CV. Mandiri Taxi and the owner of a travel car are not appropriate because it should be in a collaboration (syirkah) in addition to fulfilling the requirements and pillars, as well as responsibilities both in terms of profits and losses must be the responsibility of both parties in accordance with their respective capitals that they tasharruf.